Diversity and potential sources of microbiota associated with snow on western portions of the Greenland Ice Sheet. (4th April 2014) - Cameron, Karen A.; Hagedorn, Birgit; Dieser, Markus; Christner, Brent C.; Choquette, Kyla; Sletten, Ronald; Crump, Byron; Kellogg, Colleen; Junge, Karen
Summary: Snow overlays the majority of the Greenland Ice Sheet (GrIS). However, there is very little information available on the microbiological assemblages that are associated with this vast and climate‐sensitive landscape. In this study, the structure and diversity of snow microbial assemblages from two regions of the western GrIS ice margin were investigated through the sequencing of small subunit ribosomal RNA genes. The origins of the microbiota were investigated by examining correlations to molecular data obtained from marine, soil, freshwater and atmospheric environments and geochemical analytes measured in the snow. Snow was found to contain a diverse assemblage of bacteria ( A lphaproteobacteria, B etaproteobacteria and G ammaproteobacteria ) and eukarya ( A lveolata, F ungi, S tramenopiles and C hloroplastida ). Phylotypes related to archaeal T haumarchaeota and E uryarchaeota phyla were also identified. The snow microbial assemblages were more similar to communities characterized in soil than to those documented in marine ecosystems. Despite this, the chemical composition of snow samples was consistent with a marine contribution, and strong correlations existed between bacterial beta diversity and the concentration of Na + and Cl − . These results suggest that surface snow from western regions of Greenland contains exogenous microbiota that were likely aerosolized from more distant soil sources, transported in the atmosphere and co‐precipitated with the snow.